2021
DOI: 10.17930/agl2021222
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Evaluation of Water Quality Related to Aquatic Organisms in Comana Pond

Abstract: In the protected area Natural Park Comana located in Giurgiu County, a survey was carried out between April and June 2021, in order to analyze the water quality related to the aquatic diversity. In the samples collected from Comana Pond, several representatives belonging to four kingdoms were identified: Bacteria (blue-green algae, bacteria), Protista (single-celled and colonial green algae, diatoms, euglenoid flagellates, ciliates), Plantae (filamentous green algae, aquatic freshwater plants) and Animalia (Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…No limit value or safe interval is provided by legislation for TH either, but values between 28-84 mg CaO/L are considered optimum for aquaculture (Stone & Thomforde, 2004). Notwithstanding, determined average value (31.19 mg CaO/L) is almost double in comparison with previously reported results for other ponds (Stavrescu-Bedivan et al, 2021;Stavrescu-Bedivan et al, 2022;Sandu et al, 2023). The analysis of the results indicated that EC (µS/cm) presents very significant correlation with TH (mg CaO/L) with correlation coefficient r = 0.9230***.…”
Section: Floristic Inventorysupporting
confidence: 67%
See 4 more Smart Citations
“…No limit value or safe interval is provided by legislation for TH either, but values between 28-84 mg CaO/L are considered optimum for aquaculture (Stone & Thomforde, 2004). Notwithstanding, determined average value (31.19 mg CaO/L) is almost double in comparison with previously reported results for other ponds (Stavrescu-Bedivan et al, 2021;Stavrescu-Bedivan et al, 2022;Sandu et al, 2023). The analysis of the results indicated that EC (µS/cm) presents very significant correlation with TH (mg CaO/L) with correlation coefficient r = 0.9230***.…”
Section: Floristic Inventorysupporting
confidence: 67%
“…Water samples were collected in sterile recipients, labeled and stored at 4°C to minimize physical and chemical changes. The physico-chemical analyses of water samples were conducted as previously reported (Stavrescu-Bedivan et al, 2015), on the basis of protocols recommended for drinking water by Mănescu et al (1994). Analyses, methods and instrumentation are summarized in Table 1.…”
Section: Water Sampling and Analysesmentioning
confidence: 99%
See 3 more Smart Citations